(untitled) (Comunicação & Inovação, 2022)
The development of information and communication technologies has led to evident changes related to consumption of information in general. How have researchers dealt with this? This article aims to assess changes in the habit of reading academic journals in communities of practice in the areas of Communication and Interdisciplinary, based on a questionnaire answered by 336 members of these communities across the country.